1999
DOI: 10.1161/01.hyp.34.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoinhibitory Function of the α 2A -Adrenergic Receptor Subtype

Abstract: Abstract-Presynaptic ␣ 2 -adrenergic receptors (␣ 2 -AR) are distributed throughout the central nervous system and are highly concentrated in the brain stem, where they contribute to neural baroreflex control of blood pressure (BP). To explore the role of the ␣ 2A -AR subtype in this function, we compared BP and plasma norepinephrine and epinephrine levels in genetically engineered mice with deleted ␣ 2A -AR gene to their wild-type controls. At baseline, the ␣ 2A -AR gene knockouts (nϭ11) versus controls (nϭ10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 23 publications
7
49
0
3
Order By: Relevance
“…Animals were then placed in individual cages and allowed at least 4 h to recover from surgery. Preliminary experiments showed that extending the postsurgery period to 24 h did not change the cardiovascular parameters (unpublished results; compare also baseline values for mean arterial pressure and heart rate in the present study with Altman et al (1999) and Makaritsis et al (1999)). …”
Section: Surgerysupporting
confidence: 64%
See 1 more Smart Citation
“…Animals were then placed in individual cages and allowed at least 4 h to recover from surgery. Preliminary experiments showed that extending the postsurgery period to 24 h did not change the cardiovascular parameters (unpublished results; compare also baseline values for mean arterial pressure and heart rate in the present study with Altman et al (1999) and Makaritsis et al (1999)). …”
Section: Surgerysupporting
confidence: 64%
“…injection per se had no effect on cardiovascular parameters, showing that at least this manipulation was not a stressful stimulus. Second, loss of a 2A -adrenoceptors leads to higher resting sympathetic tone, as shown by the increased plasma noradrenaline levels and presumably also the higher baseline heart rates ( Table 2 of the present study Makaritsis et al, 1999). It seems unlikely, however, that these differences in baseline can explain the attenuated heart rate responses in a 2A -KO mice.…”
Section: Discussionmentioning
confidence: 50%
“…Several investigators showed that the ␣2A-adrenoceptor-mediated inhibition of sympathetic tone and its loss leads to a hyperadrenergic state. [25][26][27] Thus, the ␣2-adrenoceptor is required for inhibition of NE release. In the present study, the findings that subjects carrying the Asn418 allele (especially homozygous for the Asn418 allele) had higher plasma NE as well as UA compared with the subjects without the Asn418 allele are in accordance with the investigations that Asn418 of the Lys418Asn is associated with an impaired sympathoinhibitory effect on the ␣2A-presynaptic adrenoceptor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we proposed that selective α2B/C-AR agonists may represent a novel group of gastroprotective agents, which are devoid of several side effects mediated by the α2A-AR subtype, such as hypotension, bradycardia or sedation [17]. However, although the site of gastroprotective action is likely to be central, it should be considered that α2B-ARs are located also postsynaptically on vessels [18,19] and appear to be involved in the vasoconstrictor response to α2-AR agonists [20] and in salt-induced hypertension [21]. Consequently, selective α2C-AR stimulants are likely to be even more favourable and safer potential therapeutic agents against gastric mucosal injury than the mixed α2B/C-AR agonists, since they are devoid of adverse effects due to activation of both α2A-and α2B-ARs.…”
Section: Introductionmentioning
confidence: 99%